Adaptive capacity to dietary Vitamin B12 levels is maintained by a gene‐diet interaction that ensures optimal life span. Issue 1 (8th December 2021) - Nair, Tripti; Chakraborty, Rahul; Singh, Praveen; Rahman, Sabnam Sahin; Bhaskar, Akash Kumar; Sengupta, Shantanu; Mukhopadhyay, Arnab
Abstract: Diet regulates complex life‐history traits such as longevity. For optimal lifespan, organisms employ intricate adaptive mechanisms whose molecular underpinnings are less known. We show that Caenorhabditis elegans FLR‐4 kinase prevents lifespan differentials on the bacterial diet having higher Vitamin B12 levels. The flr ‐ 4 mutants are more responsive to the higher B12 levels of Escherichia coli HT115 diet, and consequently, have enhanced flux through the one‐carbon cycle. Mechanistically, a higher level of B12 transcriptionally downregulates the phosphoethanolamine methyltransferase pmt ‐ 2 gene, which modulates phosphatidylcholine (PC) levels. Pmt ‐ 2 downregulation activates cytoprotective gene expression through the p38‐MAPK pathway, leading to increased lifespan only in the mutant. Evidently, preventing bacterial B12 uptake or inhibiting one‐carbon metabolism reverses all the above phenotypes. Conversely, supplementation of B12 to E . coli OP50 or genetically reducing PC levels in the OP50‐fed mutant extends lifespan. Together, we reveal how worms maintain adaptive capacity to diets having varying micronutrient content to ensure a normal lifespan. Abstract : Multiple genes interact to maintain physiological homeostasis when Caenorhabditis elegans feeds on the varied diet it encounters in its ecological niche. Worms harboring a kinase‐dead version of the FLR‐4 protein are more responsive to the higher dietary Vitamin B12 present in Escherichia coli HT115. This boosts the flux through the one‐carbon metabolism, leading to reduction in phosphatidylcholine levels. Since the mutant FLR‐4 fails to prevent p38‐MAPK activation, these animals have better health and life span.